Peran Al-Qur'an Sebagai Sumber Etika Lingkungan: Studi Analisis Ayat-Ayat Tentang Alam Semesta - Aslam (CV. SINAR HOWUHOWU, 2025)
This study analyzes the role of the Qur'an as a source of environmental ethics by thoroughly examining verses on the universe. A qualitative approach with a textual analysis method was used to identify, interpret, and synthesize the meanings from relevant Qur'anic verses and exegetical literature. The findings reveal that the Qur'an provides a strong and holistic framework for environmental ethics, centered on the concept of Tawhid (the Oneness of God) as its spiritual foundation. The analysis further affirms that humans are entrusted with the role of khalifah (steward) on Earth, with the responsibility to maintain the mizan (balance) of nature, which is described as the